Efficient, Stable, and Ultra‐Broadband Near‐Infrared Garnet Phosphors for Miniaturized Optical Applications. Issue 16 (31st May 2022) - Dumesso, Misgana U.; Xiao, Wenge; Zheng, Guojun; Basore, Endale T.; Tang, Mingxue; Liu, Xiaofeng; Qiu, Jianrong
Abstract: Broadband near‐infrared (NIR) phosphor‐converted light‐emitting diodes (pc‐LEDs) are recently regarded as the next‐generation smart light sources for miniaturized optical applications. However, their way to practical applications is largely obstructed by the lack of efficient NIR phosphors with photoluminescence (PL) spectrum covering the whole range of 700–1100 nm. Here, an ultra‐broadband NIR phosphor is designed by rationally constructing a Cr 3+ → Yb 3+ energy transfer system in a garnet crystal Lu2 CaMg2 Ge3 O12 (LCMG). The disordering of the neighboring cations of LCMG is exploited for removing the inversion symmetry of octahedrally coordinated Cr 3+ to promote its parity‐forbidden d – d transition probability; meanwhile, efficient Cr 3+ Yb 3+ energy transfer is leveraged not only to enrich the short‐wave NIR PL in 950–1100 nm, but also to greatly improve the internal quantum efficiency (QE) (from 57.8% to 84.2%) as well as thermal stability. The resulting high external QE (35.6%) enables the demonstration of ultra‐broadband NIR pc‐LED with a record NIR output power of 93.2 mW (350 mA), which promises better performance of pc‐LEDs in non‐visible optical applications. This work provides a possible paradigm for developing ultra‐broadband NIR phosphors activated by transition metal ions. Abstract : The disordering of the neighboring cations is exploited for lowering the site symmetry of Cr 3+ to promote its parity‐forbidden d – d transition probability in garnet phosphors; meanwhile, efficient Cr 3+ Yb 3+ energy transfer is leveraged not only to enrich the short‐wave near‐infrared emission in 950–1100 nm, but also to greatly improve the internal quantum efficiency and thermal stability.